Rancang Bangun Sistem Informasi Manajemen Kru dan Produksi Syuting Berbasis Web Menggunakan Laravel serta Tailwind CSS dengan Model Waterfall (Studi Kasus: Sindikart) - Muhamad Elgar; Uus Firdaus; Setyono (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
Sindikart Equipment and Props Rental House is an artistic service company in the film industry that has been managing crew data and property inventory conventionally using office applications and cloud-based storage, which can lead to data duplication, difficulty in validating crew information, and slow retrieval of past project archives. This research aims to design and build a web-based Crew and Film Production Management Information System to integrate the management of crew data, production projects, and property inventory at Sindikart. The research method used is descriptive qualitative, with data collection through participatory observation and direct interviews with the Director of Sindikart. The system was developed using the Waterfall model, with Laravel as the backend framework, Tailwind CSS for the frontend interface, and MySQL as the database, and has two user roles, namely Admin and Crew. Testing was carried out using the Black Box Testing method on 63 test scenarios, with 62 scenarios valid and 1 scenario not yet optimal, resulting in a system success rate of 98.41%. These results indicate that the system is feasible to implement and able to transform Sindikart's operational data management into a more centralized, structured, and efficient one.